Six of one - Brown, Rita Mae 1944- (A Bantam trade paperback : novel, 1999)
Perched right on the Mason-Dixon line, tiny Runnymeade, Maryland, is ripe with a history almost as colorful as the women who live there--from Celeste Chalfonte, headstrong and aristocratic, who murders for principle and steals her brother's wife, to Fannie Jump Creighton, who runs a speakeasy right in her own home when hard times come knocking.